Negative regulation of seed germination in Medicago truncatula by the lncRNA MtCIR1 under salt stress is associated with alternative splicing - Rui Tian; Xiaohan Sun; Mingui Zhao; Wen-Hao Zhang (Plant Science, 2026)

Nitrogen fertilization and straw returning boost soil animal energy flux via distinct trait- vs. density-driven pathways - Hangle Ren; Rui Wu; Siwen Yang; Ying Liu; Weijie Zhao; Yamin Peng; Xiaohong Tian; Rui Yin (Agriculture, Ecosystems & Environment, 2026)

Using spherical protrusions for simultaneous pressure pulsation mitigation and efficiency enhancement in a giant Francis turbine across a wide load operation - Lei Tang; Xiao-Wen Huang; Rui Zhao; Tian-Yi Shi; Wen-Quan Wang (Ocean Engineering, 2026)

Maternal exposure to particulate matter during pregnancy and offspring liver function - Ziyi Zhou; Bin Sun; Yudiyang Ma; Ning Chen; Haibo Li; Wenpu Shao; Rui Tang; Lei Zheng; Meiqi Xing; Xinru Zhao; Yibing Zhu; Yaohua Tian (Environmental Pollution, 2026)

Rapid inverse design of double-curved beams for multi-stable metamaterials based on prescribed deformation histories through artificial neural network - Chun-Zheng Zhao; Xin Wang; Rui Zhang; Yongfeng Jiang; Haibo Ji; Zhen Li; Bingyang Li; Pengfei Wang; Feng Jin; Tian Jian Lu (Engineering Structures, 2026)

Genesis of the Jiawula Pb–Zn–Ag deposit in the Great Xing’an Range, NE China: constraints from fluid inclusions and S–Pb isotopes - Hongzhe Xie; Guiyuan Sun; Quzong Baima; Xinyu Gao; Ziwen Yang; Rui Tian; Lin Yang; Licheng Zhao; Zhiping Li (Journal of Asian Earth Sciences, 2026)

Prevalence and risk factors of bovine tuberculosis in dairy cattle, 2020–2025: A systematic review and meta-analysis of available literature - Qi Wang; Xiao-Nan Wang; Xiao-Qun Liu; Long-Ge Zhao; Zi-Tong Jing; Tian Tian; Jia-Ting Zhang; Yi-Xing Zhao; Jian-Ming Li; Nai-Chao Diao; Kun Shi; Rui Du (Preventive Veterinary Medicine, 2026)

A simple osmotic intervention suppresses nanoparticle-induced bacterial persistence during environmental disinfection - Rui Sun; Yijin Tian; Siyang Xue; Yueting Cui; Yunchen Zhao; Shuaishuai Li; Jiawei Yuan; Xuanxuan Zhang; Chengdong Zhang (Journal of Hazardous Materials, 2026)

Prenatal Heat Wave Exposure and Renal Function in Early Childhood: Findings from a Chinese Birth Cohort - Yibing Zhu; Rui Tang; Yudiyang Ma; Ning Chen; Xinru Zhao; Wenpu shao; Yaohua Tian; Chong Miao (Environmental Research, 2026)

Sex-specific associations between prenatal PM2.5 exposure and reproductive hormone levels in offspring aged 1–2 years: A prospective birth cohort study - Wenpu Shao; Shengli Jiang; Yudiyang Ma; Ning Chen; Zhiping Niu; Rui Tang; Meiqi Xing; Lei Zheng; Xinru Zhao; Bin Sun; Haibo Li; Ziyi Zhou; et al. (Environmental Research, 2026)

Entropy-driven engineering in AFe2O4 spinel enabling broadband microwave absorption - Xinglai Yuan; Wei Li; Qiancheng Gao; Fan Zhang; Ye Yuan; Xiaohan Wang; Yanqiu Zhu; Mi Tian; Hailong Wang; Rui Zhang; Biao Zhao; Qinghu Wang; et al. (Chemical Engineering Journal, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Light heterogeneity shapes contrasting ecological responses to photovoltaic arrays in Tibetan alpine grasslands - Lei Chen; Rui Weng; Wenhao Cong; Shuaihao Bai; Wenping Qin; Qiong Zhao; Saida Li; Yuhan Song; Jingxue Zhao; Lihua Tian (Journal of Environmental Management, 2026)

How does climate risk affect the grain production resilience: an analysis of mechanism pathways and mitigation strategies - Xiaohan Pei; Jintao Wang; Tian Qi; Rui Shi; Wenxin Liu; Minjuan Zhao (Climatic Change, 2026)

Control of zeolite local microenvironment by organofluorination engineering toward efficient c-C4F8/C3F8 separation - Rui Sun; Zicheng Wan; Yaqi Wu; Yaohan Fu; Yang Zhang; Chenyang Yang; Heng Zhao; Ziqi Tian; Liang Chen (Chemical Engineering Journal, 2026)

Reprogrammable actuation in shape memory hydrogels with soft and hard magnetic particles - Ye Tian; Yuanyuan Bian; Zike Chen; Chang Zhao; Chengqian Zhang; Yi Song; Ye Qiu; Aiping Liu; Rui Xiao; Lu Dai; Huaping Wu (Chemical Engineering Journal, 2026)

Regulation of strain infectivity in Ophiocordyceps sinensis: insights into fungal-insect symbiosis and artificial cultivation - Tianle Liu; Lijuan Wu; Xinyi Zhao; Jun Tao; Yujie Qiu; Rui Li; Yongjun Zheng; Liang Liu; Mengliang Tian (Symbiosis, 2026)

Cross-instrument coal quality spectral analysis via a PDS-assisted fine-tuning calibration transfer method - Junlong Gao; Jiaxuan Li; Jiaxin Yin; Rui Gao; Zhihui Tian; Yang Zhao; Yu Bai; Lei Dong; Weiguang Ma; Lei Zhang; Wangbao Yin; Suoteng Jia (Analytica Chimica Acta, 2026)

Curvature and Slope Control on Turbidity Currents and Sedimentation in Submarine Channels: A Numerical Study - Xinhao Wen; Yuechuan Han; Rui Zhu; Enxian Liu; Xiyan Lin; Yuchen Zhang; Yi Zhao; Yuhui Zhang; Jiajun Feng; Dongmei Tian (Journal of Marine Science and Engineering, 2026)
Submarine channels are critical conduits for sediment transport by turbidity currents, yet the quantitative influence of channel geometry on flow dynamics and sediment segregation remains poorly understood. Based on computational fluid dynamics, we constructed six three-dimensional numerical models of submarine channels with varying curvatures (R1–R3) and axial slopes (R4–R6) using ANSYS Fluent 17.2, with model settings informed by seafloor morphology from the South China Sea. The Eulerian–Eulerian multiphase model coupled with the standard k-ε turbulence model was used to simulate density fields, velocity structures, and sediment distributions. Results show that low-curvature channels exhibit symmetric density evolution and uniform sediment distribution, whereas high curvature induces pronounced asymmetry with a steep outer-bank density front and triggers secondary flow reversal. Increasing curvature also enhances flow thickness and radial mass flux. Increasing axial slope markedly elevates downstream velocity (0.09 to 0.16 m/s), reduces flow thickness, and shifts sediment distribution toward the inner bank without inducing secondary flow reversal. This study provides a parametric comparison of curvature versus slope effects on turbidity current dynamics and sedimentation patterns under fixed-bed, rectangular-channel assumptions. The findings offer a qualitative reference for interpreting sedimentary architectures in deep-water systems such as those in the South China Sea and analogous rift basins. Results are hypothesis-generating, pending further validation with field data and morphodynamic modeling.

SYVN1-provoked RASA1 ubiquitination promotes pulmonary inflammation in chronic obstructive pulmonary disease - Ju-Hong Wu; Yi-Cheng Ma; Yu-Qi Wang; Hai-Long Miao; Meng-Xue Liu; Dong-Xu Hua; Min-Min Tang; Tian-Rui Sui; Zhi-Yong Wu; Yu Wang; Jin Yang; Hui Zhao; et al. (Inflammation Research, 2026)

Effect of two double-stranded RNA viruses on the virulence of the phytopathogenic fungus Fusarium oxysporum - Jing Wang; Yunxia Ni; Xintao Liu; Hui Zhao; Xingbei Zhao; Rui Qiu; Siyuan Feng; Xiaoyuan Tian; Shouye Song; Shujun Li; Hongyan Liu (Archives of Virology, 2026)

Fluoride-ion mediated radical scavenging in a hydrophobic microenvironment for durable PEM fuel cells - Xuelin Wei; Gang Zhu; Donghao Ye; Aojie Zhang; Hao Zhang; Wangkai Zhu; Tian Tian; Shengqiu Zhao; Jiangping Song; Rui Chen; Haolin Tang (Chemical Engineering Journal, 2026)

A novel integrated model for risk analysis of soil PAHs and PTEs based on Monte Carlo simulation: a case study of Shenyang, China - Rui Zhong; Fulin Tian; Yiran Li; Zhengyu Liu; Jingyuan Wei; Hong Li; Peng Kang; Haibo Zhao; Zhisen Liu (Journal of Geochemical Exploration, 2026)

Triple-synergistic nanotherapeutics for acute and chronic colitis management via programmable multidimensional modulation - Penghui Wang; Yue Zhao; Ning Tian; Xiangling Liu; Tenghui Tian; Difu Zhu; Fangbing Liu; Hengyan Liu; Ling Li; Zhiyu Ren; Deok Chun Yang; Lei Zhao; et al. (Chemical Engineering Journal, 2026)

Dynamic electric field modulation via BaTiO3-based staggered-type heterojunction for all-solid-state lithium-sulfur batteries - Yancheng Yang; Sizhe Wang; Fei Liang; Haizhou Zhao; Yi Gu; Rujing Liu; Jian Sun; Yao Yao; Rui Tian; Haojie Song (Chemical Engineering Journal, 2026)

Four decades of Landsat data reveal the evolution of nitrogen and phosphorus components driven by human activities in the northern South China Sea - Di Tian; Xinfeng Zhao; Xingxian Li; Lei Gao; Zuobing Liang; Rui Li; Shaoheng Li; Zaizhi Yang; Chengxiang Sun; Jianyao Chen (Journal of Environmental Management, 2026)

Opposite effects of R1234yf on the flammability limits of R600a refrigerant: Experimental and kinetic insight - Xueyan Wang; Shanzhu Hu; Rui Sun; Hua Tian; Gequn Shu; Zhao Yang (International Journal of Refrigeration, 2026)

Gliadin hydrolysate-chitosan bilayer nanoparticles for berberine delivery: Controlled release, enhanced antioxidant activity, and lipid digestion regulation - Xiaoxiao Li; Yi Zhao; Aimei Liao; Yinchen Hou; Xinrui Zhang; Hailong Tian; Luyang Wang; Jin Liu; Jinyang Zhang; Jihong Huang; Rui Tan (Food Chemistry, 2026)

Imidacloprid exposure at population-relevant doses induces hepatic lipid dysregulation: Exploring the role of cGAS-STING pathway-mediated hepatocyte senescence - Yuhan Zhang; Yuqing Dai; Yihong Di; Bing Wu; Xueyan Tian; Limeng Xiong; Zeyang Bai; Jinhao Jia; Jiaming Fu; Xiaoyu Li; Yi Zhao; Hao Hu; et al. (Environmental Research, 2026)

Response of soil conservation functions to vegetation dynamics and restoration potential on the Loess Plateau - Xiaoxue Guo; Peng Tian; Guangju Zhao; Peng Gao; Chaohui Ma; Rui Shan; Jiahui Zhou; Xingmin Mu (CATENA, 2026)

Quantifying the critical regulator role of irradiation-enhanced electric field in nanoplastics aggregation with heavy metals - Yaowu Zhang; Xianzheng Yuan; Ying Tang; Xinmin Liu; Fengxin Zhao; Yan Peng; Xinping Gao; Lin Wang; Lijing Wang; Rui Tian; Rui Li; Hang Li (Water Research, 2026)

Complex magmatic system and high-melt fraction of the Changbai volcano revealed by ambient noise tomography with a dense array - Han Zhang; You Tian; Dapeng Zhao; Rui Gao (Journal of Volcanology and Geothermal Research, 2026)

Preparation of high-performance reverse osmosis membrane by “bridging” polyethylene glycol with tannic acid - Tian Wang; Rui Yu; Yanqi Gan; Zihang Zhao; Mengqi Shi; Xinxia Tian (Journal of Environmental Chemical Engineering, 2026)

Deciphering the potential risks of Yersinia enterocolitica across multi-points in food chain: prevalence, biofilm, and cross-stage transmission routes - Zhiguo Fang; Juran Mao; Zongzong Chen; Yue Wu; Xueqin Zhao; Rui Tian; Ye Lv; Xiao Xiao; Jiaqi Yan; Xiuqin Lou; Jun Li (Food Research International, 2026)

Antioxidant activity and emulsifying properties of Dendrobium officinale polysaccharides with distinct structural characteristics - Cunchao Zhao; Weiqian Wang; Fanrui Li; Jun Sheng; Rui He; Lijun You; Yang Tian (Food Chemistry, 2026)

The potential relationships between soil microbial communities and seed germination in the floodplain wetlands - Meng-Li Wang; Rui-Si Zhao; Xiao-Kan Wang; Jia-Ying Tian; Qian-Kun Hu; Long-Yi Yuan; You-Cai Xiong; Ai-Tian Ren (Plant and Soil, 2026)

Phosphorus fertilization shapes rhizosphere beneficial microbial communities and soil–plant relations in arid cotton fields of Xinjiang, China - Bin Peng; Shuai Zhao; Cong-Rui Liu; Wen-Xuan Mai; Na Zhou; Ping Zhang; Shu-Ying Wang; Xu Liu; Bao-Zhan Wang; Chang-Yan Tian (Plant and Soil, 2026)

Tracing sediment sources during rainfall events in a northern Loess Plateau catchment using geochemical and mid-infrared spectral methods - Rui Shan; Peng Tian; Ang Lu; Xiaoxue Guo; Xingmin Mu; Haoyu Zhu; Geng Ren; Guangju Zhao (Journal of Mountain Science, 2026)

Grassland soil seed bank responses to grazing exclusion: a global synthesis - Jishuai Su; Lixin Yu; Rui Tian; Wanbing Liu; Ruolin Zhao; Menghan Niu; Zekai Yang; Yi Zhang; Fengwei Xu; Heyong Liu; Yong Jiang (Journal of Environmental Management, 2026)

Dietary components cooperate with intestinal flora to regulate food allergy - Jiaxi Yan; Li Niu; Wei Wang; Rui Gao; Jianxiong Hao; Huan Rao; Dandan Zhao; Xueqiang Liu; Wentong Xue; Yang Tian (Food Chemistry, 2026)

Machine learning-assisted the directed evolution of descriptor for Mg-CO2 batteries - Zhe Xue; Rui Tan; Ming Ji; Jinzhong Tian; Hua Hou; Xinyu Zhang; Lianfeng Zou; Yuhong Zhao (Chemical Engineering Journal, 2026)

Discovery of lignans and curcuminoids as the effective inhibitors of pancreatic lipase: structure-activity relationship and inhibitory mechanism - Jie Mu; Rui-Dong Wang; Yi-Shu Zhao; Tian-Chi Lu; Si-Si Chen; Yi-Jing Wang; Hua Wei; Li-Wei Zou (Natural Product Research, 2025)

Four new dammarane nortriterpenoids isolated from mastic ( Pistacia lentiscus L.) and their anti-inflammatory and cytotoxic activities - Xue Tian; Xue-Rui An; Zhi-Qiang Zhao; Jian-Hua Fan; Su-Ning Yuan; Tian-Zhi Li; Wei Liu (Natural Product Research, 2025)

Molecular sensory basis of the smoky aroma in sesame oil elucidated by combining SAFE-GC-O-MS, σ-τ plot, and computational simulations - Tian-Pei Zhao; Tong-Yu Wang; Yi Jiang; Yi-Fei Wang; Shu-Rui Zhang; Jing-Yu Chen; Yue-Hua Li; Xue-De Wang; Hua-Min Liu; Hong-Wei Liu; Ke-Qing Liu (Food Research International, 2025)

A high strength, breathable, water resistant chitosan-gelatin composite film modified by tannic acid-synergistic ZIF-8 for blueberry preservation - Huixuan Zhang; Xue Yang; Yingying Zhang; E. Zhao; Haimiao Tian; Keshan Wang; Ning Ji; Yuanyuan Liu; Rui Wang (Food Packaging and Shelf Life, 2025)

Imidacloprid induces abnormal glucose metabolism through NF-κB-mediated apoptosis of pancreatic β cells based on population exposure levels - Zhongyuan Zhang; Jiaming Fu; Yihong Di; Honghui Li; Bing Wu; Xueyan Tian; Meiyan Li; Yuqing Dai; Zhuoheng Shen; Jinhao Jia; Zeyang Bai; Limeng Xiong; et al. (Environmental Research, 2025)

Superacid polymer electrolyte with end-group-protected proton sites mitigates ammonia poisoning for efficient electrochemical hydrogen separation from ammonia cracking reformate gas - Jiaqi Shuai; Hao Li; Zhengrui Xiao; Zeqi You; Yucong Liao; Rui Wang; Yafeng Li; Yuanwei Yan; Jiangping Song; Tian Tian; Lan Zhang; Siew Hwa Chan; et al. (Chemical Engineering Journal, 2025)

CRP and HNF1A collaborate to regulate the progression of laryngeal cancer through the Wnt signaling pathway - Zhigang Zhao; Xiaojing Zhu; Jinyuan Xu; Penglong Song; Yanan Sun; Zhenming Yang; Li Wang; Jiarui Zhang; Rui Zhao; Xiaoxue Chen; Wenjing Li; Linli Tian; et al. (Functional & Integrative Genomics, 2025)

Enhanced electrocatalytic oxidation of high-salinity quaternary ammonium compound wastewater using CNTs-(Ru Ir O2)/Ti Anode - Hao-Tian Liu; Han-Qing Zhao; Yi-Rui Yang; Shuang Wu; Jia-Ping Huang; Rui-Han Yu; Hongcheng Bai; Aqiang Ding; Daijun Zhang; Peili Lu (Journal of Environmental Sciences, 2025)

Millimeter-scale interactions of nitrogen and potassium on denitrification, anammox, and Feammox in soil fertilization zones - Jingjing Lyu; Rui Tian; Runhua Zhang; Peng Chen; Xinxin Jing; Runqin Zhang; Kang Zhao; Yi Liu; Chenhao Lyu; Zhiguo Li (Journal of Environmental Sciences, 2025)

Recent research progress of methane dry reforming to syngas - Yan Wang; Rui Li; Chunyang Zeng; Wenjuan Sun; Hui Fan; Qingxiang Ma; Tian-Sheng Zhao (Fuel, 2025)

Acute high-altitude hypoxia induced NLRP3 inflammasome activation in pulmonary artery smooth muscle cells by BMAL1 targeting mitochondrial VDAC1-mediated MtDNA leakage - Si-Yuan He; Ying-Rui Bu; Jin Xu; Yu-Meng Wang; Tian-Xi Feng; Pei-Jie Li; Yi-Xiao Zhao; Yi-Ling Ge; Man-Jiang Xie (Apoptosis, 2025)

Earthworms mitigate drought effects on microbial decomposition of straw under varying microplastic conditions - Chuanxiong Huang; Weijie Zhao; Hangle Ren; Rui Wu; Ying Liu; Hongxin Xu; Benhua Sun; Jianglan Shi; Xiaohong Tian; Rui Yin (Journal of Hazardous Materials, 2025)

A vision foundation model-based method for large-scale forest disturbance mapping using time series Sentinel-1 SAR data - Yuping Tian; Feng Zhao; Ran Meng; Rui Sun; Yuan Zhang; Yanyan Shen; Bin Wang; Jie Liu; Mingze Li (Remote Sensing of Environment, 2025)

Climate-driven spatiotemporal variation of soil erodibility in China - Lili Qu; Zheng Sun; Zhiyuan Tian; J.M. Schoorl; Rui Ma; Yan Zhao; Yihang Wu; Yin Liang (Environmental Impact Assessment Review, 2025)

Holographic approach for three-dimensional magnetotelluric modeling and CPU-GPU Parallel Architecture - De-Xiang Zhu; Shi-Kun Dai; Hong-Jun Tian; Qing-Rui Chen; Wen-Xue Zhao (Applied Geophysics, 2025)

Impact of soil erosion-driven degradation on crop yield in black soils of Northeast China's Songnen Plain - Yan ZHAO; Zhiyuan TIAN; Rui MA; Lili QU; Yihang WU; Yin LIANG (Pedosphere, 2025)

Evolution of and mechanisms controlling water chemistry in the Beijiang River Basin over the past four decades - Zaizhi Yang; Tao Jiang; Zuobin Liang; Xinfeng Zhao; Kun Ren; Di Tian; Lei Gao; Qirui Wu; Shaoheng Li; Rui Li; Lichun Xie; Jianyao Chen (Journal of Geochemical Exploration, 2025)

Hydrophobically modified Cu-ZnO-Al2O3 catalyst for CO2 hydrogenation to methanol - Xiuyun Jiang; Jucang Ke; Rui Li; Hao Huang; Zhihao Liu; Haozhe Feng; Qingxiang Ma; Xinhua Gao; Guangbo Liu; Xiaobo Feng; Tian-Sheng Zhao; Noritatsu Tsubaki (Journal of Environmental Chemical Engineering, 2025)

Cement-mortar lining failure and metal release caused by electrochemical corrosion of ductile iron pipes in drinking water distribution systems - Hao Guo; Rui Wang; Menghan Jiang; Yimei Tian; Yapeng Jin; Weigao Zhao; Chenwan Wang; Jianhua Yin (Journal of Environmental Sciences, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Cascading environmental, phenological, and physiological influences on spatial variability of annual gross primary productivity in the Northern Hemisphere - Lang Han; Gui-Rui Yu; Zhi Chen; Qiu-Feng Wang; Xian-Jin Zhu; Wei-Kang Zhang; Tie-Jun Wang; Zhi-Feng Yan; Tian-You Zhang; Shi-Ping Chen; Hui-Min Wang; Jun-Hua Yan; et al. (Science of The Total Environment, 2025)

Isotope tracer study of soil erosion in a typical sub-watershed in the eastern Tianshan Mountains, China - Ninglu Zhang; Jianjun Yang; Wenli Xing; Xinyu Liu; Feifei Sheng; Wanqing Zhao; Zhiguang Zhang; Ziqi Tian; Rui Chen (Journal of Environmental Radioactivity, 2025)

Identifying spatial drivers of soil heavy metal pollution risk integrating positive matrix factorization, machine learning, and multi-scale geographically weighted regression - Yujie Pan; Anmeng Sha; Wenjing Han; Chang Liu; Guowangchen Liu; Emily Welsch; Min Zeng; Shasha Xu; Yi Zhao; Shang Tian; Yiyi Li; Rui Deng; et al. (Journal of Hazardous Materials, 2025)

A novel framework for river organic carbon retrieval through satellite data and machine learning - Shang Tian; Anmeng Sha; Yingzhong Luo; Yutian Ke; Robert Spencer; Xie Hu; Munan Ning; Yi Zhao; Rui Deng; Yang Gao; Yong Liu; Dongfeng Li (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Deciphering the mineral code of urinary stones: A first look at zinc isotopes - Ziyang Ding; Guilin Han; Yu Tian; Rui Qu; Jinke Liu; Di Wang; Ye Zhao (Environmental Pollution, 2025)

The flavonoid metabolic pathway genes Ac4CL1, Ac4CL3 and AcHCT1 positively regulate the kiwifruit immune response to Pseudomonas syringae pv. actinidiae - Chao Ma; Wei Liu; Xiaofei Du; Chao Zhao; Runze Tian; Rui Li; Chenxiao Yao; Lili Huang (Plant Molecular Biology, 2025)

Sleep deprivation stimulates adaptive thermogenesis by activating AMPK pathway in mice - Tian-Shu Zheng; Xin-Ran Gao; Rui-Ping Xu; Yi-Fei Zhao; Zhi-Teng Yang; De-Hua Wang (Journal of Comparative Physiology B, 2025)

Molecular mechanisms behind the inhibitory effects of ginsenoside Rg3 on hepatic fibrosis: a review - Zhao-feng Tian; Rui-yi Hu; Zi Wang; Ya-jun Wang; Wei Li (Archives of Toxicology, 2025)

Organic matter accumulation driven by land-sea interactions during the Late Cretaceous: A geochemical study of the Nenjiang Formation, Songliao Basin - Congsheng Bian; Shiju Liu; Wei Liu; Xiong Cheng; Xin Liu; Jin Dong; Rui Wang; Yongxin Li; Ming Guan; Qianhui Tian; Wenzhi Zhao (Organic Geochemistry, 2025)

Insight into the effect of humic acids on transport of Cd2+ in biochar-amended saturated porous media - Tian Zhao; Yongyang Liu; Rui Liu; Fang Wang (Journal of Soils and Sediments, 2025)

The legacy effect of long-term nitrogen fertilization on nitrous oxide emissions - Xue Tian; Huanhuan Wei; Yibai Zhao; Rui Cao; Chong Zhang; Xiaotong Song; Di Wu; Klaus Butterbach-Bahl; Robert M. Rees; Pete Smith; Xiaotang Ju (Science of The Total Environment, 2024)

Contrasting fracturing and cementation timings during shale gas accumulation and preservation: An example from the Wufeng-Longmaxi shales in the Fuling shale gas field, Sichuan Basin, China - Tao Luo; Xiaowen Guo; Zhiliang He; Jian-xin Zhao; Ze Tao; Tian Dong; Rui Yang; Junlin Chen (Marine and Petroleum Geology, 2024)

The role of probiotics in the treatment of non-alcoholic fatty liver disease (NAFLD): New insights based on meta-analysis and subgroup analysis - Rui Xiao; Yang Cao; Linlin Wang; Peijun Tian; Qixiao Zhai; Jianxin Zhao; Gang Wang; Yu Zhu (Food Bioscience, 2024)

Myosuppressin signaling deficiency affects ovarian development via repression of 20-hydroxyecdysone biosynthesis in Grapholita molesta - Jie Cheng; Jing-Kai Liu; Tian-Li Wang; Wei Wei; Hui-Ming Xiang; Xian-Wei Li; Rui-Yan Ma; Zhi-Guo Zhao (Pesticide Biochemistry and Physiology, 2024)

High density cobalt single atom catalysts for H2O2 electrosynthesis: A critical design of carbon nitride skeleton - Zhe Xue; Rui Tan; Jinzhong Tian; Hua Hou; Xinyu Zhang; Yuhong Zhao (Chemical Engineering Journal, 2024)

Elevating electrochemical performance of Na4MnCr(PO4)3 cathode material for sodium ion batteries through the synergistic effect of Sc doping and RuO2/C coating - Qing Zhu; Jinxin Wu; Rui Tong; Xiuli Hu; Ningchen Tian; Botian Liu; Jiqiong Jiang; Yanwei Li; Jianwen Yang; Jianwei Zhao (Chemical Engineering Journal, 2024)

Specific and Plastic: Chandelier Cell-to-Axon Initial Segment Connections in Shaping Functional Cortical Network - Yanqing Qi; Rui Zhao; Jifeng Tian; Jiangteng Lu; Miao He; Yilin Tai (Neuroscience Bulletin, 2024)
Axon initial segment (AIS) is the most excitable subcellular domain of a neuron for action potential initiation. AISs of cortical projection neurons (PNs) receive GABAergic synaptic inputs primarily from chandelier cells (ChCs), which are believed to regulate action potential generation and modulate neuronal excitability. As individual ChCs often innervate hundreds of PNs, they may alter the activity of PN ensembles and even impact the entire neural network. During postnatal development or in response to changes in network activity, the AISs and axo-axonic synapses undergo dynamic structural and functional changes that underlie the wiring, refinement, and adaptation of cortical microcircuits. Here we briefly introduce the history of ChCs and review recent research advances employing modern genetic and molecular tools. Special attention will be attributed to the plasticity of the AIS and the ChC-PN connections, which play a pivotal role in shaping the dynamic network under both physiological and pathological conditions.

Response of soil quality degradation to cultivation and soil erosion: A case study in a Mollisol region of Northeast China - Rui Ma; Zhiyuan Tian; Yan Zhao; Yihang Wu; Yin Liang (Soil and Tillage Research, 2024)

Sunflower-YOLO: Detection of sunflower capitula in UAV remote sensing images - Rui Jing; Qinglin Niu; Yuyu Tian; Heng Zhang; Qingqing Zhao; Zongpeng Li; Xinguo Zhou; Dongwei Li (European Journal of Agronomy, 2024)

A novel method of fuel consumption prediction for wing-diesel hybrid ships based on high-dimensional feature selection and improved blending ensemble learning method - Tian Lan; Lianzhong Huang; Ranqi Ma; Zhang Ruan; Shan Ma; Zhongwei Li; Haoyang Zhao; Cong Wang; Rui Zhang; Kai Wang (Ocean Engineering, 2024)

Propane dehydrogenation performance of titanosilicate-1 supported CoOx catalysts by adjusting the acidity and reducibility - Xue Cai; Yongzheng Zhao; Lili Cai; Xiaoyan Tian; Cunzi Wei; Dandan Qin; Meitong Li; Rui Tao; Wenling Chu; Weishen Yang (Fuel, 2024)

Progressive Freezing-Melting Method for Removal Boron from Simulated Seawater - Yihong Zou; Yan Zhang; Chen Zhao; Rui Mei; Lin Lin; Chunbo Liu; Yucan Liu; Yepeng Tian; Futian Chen (Water, Air, & Soil Pollution, 2024)

Shoot and Root Traits are Associated with Varying Soil Phosphorus Supply in Chinese Cabbage - Hou Sai-sai; Pu Zi-tian; Zhang Rui-fang; Zhang Chi; Wang Hong; Wang Xin-xin; Zhao Jian-jun (Journal of Soil Science and Plant Nutrition, 2024)

Diagnostic performance of mpox virus (MPXV) real-time PCR assays: multicenter assessment and extended sensitivity analysis - Ziqiang Li; Yuqing Chen; Yanxi Han; Zhenli Diao; Tao Huang; Lei Feng; Yu Ma; Cong Liu; Meng Tian; Jing Li; Wanyu Feng; Zihong Zhao; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2024)

Micronutrient perspective on COVID-19: Umbrella review and reanalysis of meta-analyses - Yafei Xie; Jianguo Xu; Dan Zhou; Mingyue Guo; Mengxiang Zhang; Ya Gao; Ming Liu; Jiyuan Shi; Kelu Yang; Qingyong Zheng; Liang Zhao; Yu Qin; et al. (Critical Reviews in Food Science and Nutrition, 2024)

Structurally diverse 1,2-diarylpropanes from the fruit of Crataegus pinnatifida and the investigation on their mirror-image ECD spectra with the same absolute configurations - Tian-Ming Lv; Rui Guo; Bo-Han Yang; Peng Zhao; Bin Lin; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2024)

A randomised double-blind placebo-controlled trial of a probiotic combination for manipulating the gut microbiota and managing metabolic syndrome - Rui Xiao; Ying Chen; Xiaofeng Zhu; Linlin Wang; Peijun Tian; Xing Jin; Ming Liang; Zehua Chen; Ting Zhang; Long Qian; Qun Wang; Jianxin Zhao; et al. (Food Bioscience, 2024)

The isomorphous substitution of Si(4Al) with P in FAU zeolite and its stabilization effect - Qiang Zhang; Hongjuan Zhao; Xingyu Liu; Rui Li; Tian Xia; Yue Ma; Yuren Wang; Kang Chen; Jiujiang Wang; Penghui Zeng; Honghai Liu; Chaowei Liu; et al. (Chemical Engineering Journal, 2024)

Analysis of landslide deformation in eastern Qinghai Province, Northwest China, using SBAS-InSAR - Haibo Tian; Pinglang Kou; Qiang Xu; Yuxiang Tao; Zhao Jin; Ying Xia; Jiangfan Feng; Rui Liu; Yongcheng Gou (Natural Hazards, 2024)

The pH adjustment of Vitis amurensis dry red wine revealed the evolution of organic acids, volatomics, and sensory quality during winemaking - Meng-Bo Tian; Rui-Qi Hu; Zhao-Long Liu; Ning Shi; Hao-Cheng Lu; Chang-Qing Duan; Jun Wang; Yan-Feng Sun; Qing-Sen Kong; Fei He (Food Chemistry, 2024)

An efficient synthesis and organic-modification coupling strategy to produce highly dispersed ultrathin antioxidant intercalated layered double hydroxides for enhancing performance of polypropylene composites - Zijia Li; Menghua Zhao; Rui Tian; Yalin Shi; Weiliang Tian; Yiqing Bai; Meng Xu; Kai Xu; Dali Gao; Yongjun Feng (Chemical Engineering Journal, 2024)

Estimation of water quality variables based on machine learning model and cluster analysis-based empirical model using multi-source remote sensing data in inland reservoirs, South China - Di Tian; Xinfeng Zhao; Lei Gao; Zuobing Liang; Zaizhi Yang; Pengcheng Zhang; Qirui Wu; Kun Ren; Rui Li; Chenchen Yang; Shaoheng Li; Meng Wang; et al. (Environmental Pollution, 2024)

Function-oriented bifunctional Mg & MoP modified polymeric carbon nitride for selective photoreduction CO2 to CH4 - Jun-ying Tang; Wei-guo Pan; Yu-lian He; Tian-shuo Zhao; Qing-shan Wang; Rui-tang Guo (Chemical Engineering Journal, 2024)

Source characteristics of polycyclic aromatic hydrocarbons and polychlorinated biphenyls in surface soils of Shenyang, China: A comparison of two receptor models combined with Monte Carlo simulation - Yiran Li; Fulin Tian; Rui Zhong; Haibo Zhao (Journal of Hazardous Materials, 2024)

A portable on-demand therapeutic nitric oxide generation apparatus: New strategy for diabetic foot ulcers - Huihui Bian; Junjie Wang; Xiaodong Shan; Xiuqing Li; Yongjin Wang; Rui Sun; Chongxian Wang; Juan Lv; Chunlei Xing; Chunlei Hui; Dinglei Zhang; Chenxi Zhang; et al. (Chemical Engineering Journal, 2024)

The co-regulation of the gut microbiome and host genes might play essential roles in metformin gastrointestinal intolerance - Huixiang Zhang; Jiao Lai; Lihuan Zhang; Wei Zhang; Xun Liu; Qilin Gong; Hongxi Tian; Mingzhi Yang; Tao Yang; Rui Zhao; Dongqing Li; Hehua Huang; et al. (Toxicology and Applied Pharmacology, 2023)

Experimental study on enhanced coal seam gas extraction by uniform pressure/pulse pressure N2 injection - Peng-fei Ji; Hai-fei Lin; Xiang-guo Kong; Shu-gang Li; Yu-chu Cai; Rui-zhe Wang; Yu Tian; Tian-shuo Zhao (Fuel, 2023)

A new anchor-siphon drainage combined method used for slope stabilization - Hong-yue Sun; Xu Wang; Yang Yu; Jun-wei Shu; Tian-long Wang; Rui Luo; Zhao-wei Chu (Journal of Mountain Science, 2023)

Rapid determination of the relative configuration of diverse 8,4′-oxyneolignans by NMR analysis: Retrospective studies, improvement and structural revision - Peng Zhao; Li-Li Lou; Ben-Song Xin; Zhi-Yuan Li; Rui Guo; Wei-Yu Zhou; Tian-Ming Lv; Xiao-Xiao Huang; Shao-Jiang Song (Phytochemistry, 2023)

Anti-ice-pinning superhydrophobic surfaces for extremely low ice adhesion - Ze Tian; Peixun Fan; Dongyu Zhu; Lizhong Wang; Huanyu Zhao; Changhao Chen; Rui Peng; Daizhou Li; Hongjun Zhang; Minlin Zhong (Chemical Engineering Journal, 2023)

Farmers’ participation into the recovery of waste agricultural plastic film: An application of the Theory of Planned Behavior - Ze-Ying Zhao; Wen-Bo Li; Peng-Yang Wang; Hong-Yan Tao; Rui Zhou; Jin-Ying Cui; Jian Zhang; Tao Tian; Xu-Zhe Zhao; Yi-Bo Wang; You-Cai Xiong (Waste Management, 2023)

Regeneration of high-performance materials for electrochemical energy storage from assorted solid waste: A review - Jia-feng Zhang; De-zhao Peng; Xiang-gang Gao; Jing-tian Zou; Long Ye; Guan-jun Ji; Bi Luo; Gui-hui Yu; Peng-fei Li; Xiao-wei Wang; Zao-wen Zhao; Bao Zhang; et al. (Journal of Cleaner Production, 2023)

Comprehensive understanding of tetracycline hydrochloride adsorption mechanism onto biochar-based gel pellets based on the combination of characterization-based and approximate site energy distribution methods - Bai-Qin Zhou; Qian-Qian Sang; Yu-Jun Wang; Hui Huang; Fang-Jun Wang; Rui-Chun Yang; Yuan-Tian Zhao; Zi-Jie Xiao; Chun-Yue Zhang; Hui-Ping Li (Journal of Cleaner Production, 2023)

Generation of gridded temperature map of constant-temperature layer based on meteorological data for shallow geothermal applications - Rui Mao; Zilong Zhao; Lei Tian; Tiantian Fang; Xinlei Wang (Geothermics, 2023)

Expression and functional analysis of ace1 and ace2 reveal their differential roles in larval growth and insecticide sensitivity in Spodoptera frugiperda (J. E. Smith, 1797) - Jie Gao; Li-Feng Gong; Huan-Huan Wang; Rui Zhao; Xing Xiao; Xin-Yao Tian; Bo Li; Pei Liang; Xi-Wu Gao; Shao-Hua Gu (Journal of Pest Science, 2023)

Moringa oleifera Lam. leaves as new raw food material: A review of its nutritional composition, functional properties, and comprehensive application - Min Yang; Liang Tao; Xin-Rui Kang; Zi-Lin Wang; Ling-Yan Su; Ling-Fei Li; Fan Gu; Cun-Chao Zhao; Jun Sheng; Yang Tian (Trends in Food Science & Technology, 2023)

Corrigendum to “Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char” [J. Hazard. Mater. 447 (2023) 130772] - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Application of Clostridium butyricum, Rummeliibacillus suwonensis, and Issatchenkia orientalis for Nongxiangxing baijiu fermentation: Improves the microbial communities and flavor of upper fermented grain - Tongwei Guan; Xiaotian Wu; Rui Hou; Lei Tian; Qiao Huang; Fan Zhao; Ying Liu; Shirong Jiao; Shuangquan Xiang; Jiaxu Zhang; Dong Li; Jing Luo; et al. (Food Research International, 2023)

Strontium isotope ratios in kidney stones reveal the environmental implications for humans in Beijing, China - Rui Qu; Guilin Han; Yu Tian; Ye Zhao (Environmental Geochemistry and Health, 2023)

Experimental study on flow and heat transfer of supercritical carbon dioxide in zigzag channels with bending angle 30° for advanced nuclear systems - Sheng-hui Liu; Rui-long Liu; Yan-ping Huang; Xiao-liang Zhu; Liu Yang; Jia Tang; Bin Han; Tian-yang Xing; Xue-bin Zhao (Annals of Nuclear Energy, 2023)

Biomarkers of aging - Hainan Bao; Jiani Cao; Mengting Chen; Min Chen; Wei Chen; Xiao Chen; Yanhao Chen; Yu Chen; Yutian Chen; Zhiyang Chen; Jagadish K. Chhetri; Yingjie Ding; et al. (Science China Life Sciences, 2023)

Efficient lead immobilization by bio-beads containing Pseudomonas rhodesiae and bone char - Junpeng Li; Rui Bai; Wei Chen; Chongyuan Ren; Fan Yang; Xiaochun Tian; Xiaofeng Xiao; Feng Zhao (Journal of Hazardous Materials, 2023)

Polycyclic aromatic hydrocarbon exposure burden: Individual and mixture analyses of associations with chronic obstructive pulmonary disease risk - Kun Peng; Zhao Li; Tian-Rui Gao; Jia Lv; Wen-Jing Wang; Ping Zhan; Wen-Cong Yao; Hui Zhao; Hua Wang; De-Xiang Xu; Yichao Huang; Zhu-Xia Tan (Environmental Research, 2023)

Understanding the Origin and Evolution of Tea (Camellia sinensis [L.]): Genomic Advances in Tea - Zai-Bao Zhang; Tao Xiong; Jia-Hui Chen; Fan Ye; Jia-Jia Cao; Yu-Rui Chen; Zi-Wei Zhao; Tian Luo (Journal of Molecular Evolution, 2023)

Cross-subject aesthetic preference recognition of Chinese dance posture using EEG - Jing Li; Shen-rui Wu; Xiang Zhang; Tian-jian Luo; Rui Li; Ying Zhao; Bo Liu; Hua Peng (Cognitive Neurodynamics, 2023)

Reduced plastic film mulching under zero tillage boosts water use efficiency and soil health in semiarid rainfed maize field - Ai-Tian Ren; Ji-Yuan Li; Ling Zhao; Rui Zhou; Jian-Sheng Ye; Yi-Bo Wang; Xu-Cheng Zhang; Kiprotich Wesly; Ming-Sheng Ma; You-Cai Xiong (Resources, Conservation and Recycling, 2023)

Antimicrobial activity and mechanism of preservatives against Alicyclobacillus acidoterrestris and its application in apple juice - Zhouli Wang; Yu Tian; Qi Wang; Tianmin Guo; Yahong Yuan; Tianli Yue; Hang Jia; Qian Ge; Zidan Zhao; Rui Cai (International Journal of Food Microbiology, 2023)

Low-cost mineral packing materials improve DOM and micropollutants removal from landfill leachate in ozonation bubble columns: Insights into the enhancement mechanisms and applicability of surrogate-based monitoring - Xuetong Yang; Changtao Chen; Tao Zhang; Xiang Tian; Rui Zhang; Dave Manhaeghe; Yunliang Zhao; Shaoxian Song; Kristof Demeestere; Stijn W.H. Van Hulle (Chemical Engineering Journal, 2023)

A Medicago truncatula lncRNA MtCIR1 negatively regulates response to salt stress - Rui Tian; Xiaohan Sun; Cuimei Liu; Jinfang Chu; Mingui Zhao; Wen-Hao Zhang (Planta, 2023)

All-in-one additive enables defect passivated, crystallization modulated and moisture resisted perovskite films toward efficient solar cells - Chuanming Tian; Yu Zhao; Xuefei Han; Bin Li; Yichuan Rui; Hao Xiong; Yu Qiu; Wei An; Kerui Li; Chengyi Hou; Yaogang Li; Hongzhi Wang; et al. (Chemical Engineering Journal, 2023)

Rationally tailoring anion traps into electrospun nanofibers for highly efficient perrhenate/pertechnetate capture - Dingyang Chen; Zhaoli Liu; Shuying Li; Xiaofei Jing; Yuyang Tian; Wei Hu; Fengchao Cui; Rui Zhao; Guangshan Zhu (Chemical Engineering Journal, 2023)

Precise orbit determination for BDS-3 GEO satellites enhanced by intersatellite links - Xiaojie Li; Xiaogong Hu; Rui Guo; Chengpan Tang; Shuai Liu; Jie Xin; Jinglei Guo; Yijun Tian; Yufei Yang; Jianhua Yang; Xinglong Zhao (GPS Solutions, 2023)

Solar ring mission: Building a panorama of the Sun and inner-heliosphere - Yuming Wang; Xianyong Bai; Changyong Chen; Linjie Chen; Xin Cheng; Lei Deng; Linhua Deng; Yuanyong Deng; Li Feng; Tingyu Gou; Jingnan Guo; Yang Guo; et al. (Advances in Space Research, 2023)

Leakage Fault Diagnosis of Lifting and Lowering Hydraulic System of Wing-Assisted Ships Based on WPT-SVM - Ranqi Ma; Haoyang Zhao; Kai Wang; Rui Zhang; Yu Hua; Baoshen Jiang; Feng Tian; Zhang Ruan; Hao Wang; Lianzhong Huang (Journal of Marine Science and Engineering, 2022)
Wing-assisted technology is an effective way to reduce emissions and promote the decarbonization of the shipping industry. The lifting and lowering of wing-sail is usually driven by hydraulic system. Leakage, as an important failure form, directly affects the safety as well as the functioning of hydraulic system. To increase the system reliability and improve the wing-assisted effect, it is essential to conduct leakage fault diagnosis of lifting and lowering hydraulic system. In this paper, an AMESim simulation model of lifting and lowering hydraulic system of a Very Large Crude Carrier (VLCC) is established to analyze the operation characteristics of the hydraulic system. The effectiveness of the model is verified by the operation data of the actual hydraulic system. On this basis, a wavelet packet transform (WPT)-based sensitive feature extracting method of leakage fault for the hydraulic system is proposed. Subsequently, a support vector machine (SVM)-based multi-classification model and diagnosis method of leakage fault are proposed. The study results show that the proposed method has an accuracy of as high as 97.5% for six leakage fault modes. It is of great significance for ensuring the reliability of the wing-sail operation and improving the utilization rate of the offshore wind resources.

Efficacy and Safety of Recombinant Human Prourokinase in Acute Ischemic Stroke: A Phase IIa Randomized Clinical Trial - Haiqing Song; Yuan Wang; Qingfeng Ma; Huisheng Chen; Bo Liu; Yi Yang; Jianguo Zhu; Shigang Zhao; Xiaoping Jin; Yongqiu Li; Yanyong Wang; Runxiu Zhu; et al. (Translational Stroke Research, 2022)

Direct Radiative Effects of Dust Aerosols over Northwest China Revealed by Satellite-Derived Aerosol Three-Dimensional Distribution - Rui Jia; Yuzhi Liu; Yan Li; Jun Li; Xiaolin Hu; Ronglu Gao; Yunfei Tian; Yanling Sun; Nannan Mu; Minfen Zhao (Journal of Meteorological Research, 2022)

MicroRNA alteration in cerebrospinal fluid from comatose patients with traumatic brain injury after right median nerve stimulation - Ying Jia; Yi-fan He; Ye Tian; Yuan-zhi Wang; Rui-ting Zhao; Xiao-chun Li; Jian Sun; Ying-sheng Wei; Shuo An; Heng-jie Yuan; Chun-xiao Wan; Rong-cai Jiang (Experimental Brain Research, 2022)

Homocysteine-Induced Disturbances in DNA Methylation Contribute to Development of Stress-Associated Cognitive Decline in Rats - Shi-Da Wang; Xue Wang; Yun Zhao; Bing-Hua Xue; Xiao-Tian Wang; Yu-Xin Chen; Zi-Qian Zhang; Ying-Rui Tian; Fang Xie; Ling-Jia Qian (Neuroscience Bulletin, 2022)

Toxic encephalopathy induced by radix Sophorae tonkinensis - Xue-Lin Li; Hao-Tian Zhao; Jinming Han; Zhong-Rui Yan; Hai-Yang Wang (Acta Neurologica Belgica, 2022)

Positron Emission Tomography Molecular Imaging for Phenotyping and Management of Lymphoma - Xiaohui Zhang; Han Jiang; Shuang Wu; Jing Wang; Rui Zhou; Xuexin He; Shufang Qian; Shuilin Zhao; Hong Zhang; Ali Cahid Civelek; Mei Tian (Phenomics, 2022)

Dysfunction of FadA‐cAMP signalling decreases Aspergillus flavus resistance to antimicrobial natural preservative Perillaldehyde and AFB1 biosynthesis - Kunlong Yang; Qingru Geng; Yue Luo; Rui Xie; Tongzheng Sun; Zhen Wang; Ling Qin; Wei Zhao; Man Liu; Yongxin Li; Jun Tian (Environmental Microbiology, 2022)
Summary Aspergillus flavus is an opportunistic fungal pathogen that colonizes agriculture crops with aflatoxin contamination. We found that Perillaldehyde (PAE) effectively inhibited A . flavus viability and aflatoxin production by inducing excess reactive oxygen species (ROS). Transcriptome analysis indicated that the Gα protein FadA was significantly induced by PAE. Functional characterization of FadA showed it is important for asexual development and aflatoxin biosynthesis by regulation of cAMP‐PKA signalling. The Δ fadA mutant was more sensitive to PAE, while Δ pdeL and Δ pdeH mutants can tolerate excess PAE compared to wild‐type A . flavus . Further RNA‐sequence analysis showed that fadA was important for expression of genes involved in oxidation–reduction and cellular metabolism. The flow cytometry and fluorescence microscopy demonstrated that Δ fadA accumulated more concentration of ROS in cells, and the transcriptome data indicated that genes involved in ROS scavenging were downregulated in Δ fadA mutant. We further found that FadA participated in regulating response to extracellular environmental stresses by increasing phosphorylation levels of MAPK Kinase Slt2 and Hog1. Overall, our results indicated that FadA signalling engages in mycotoxin production and A . flavus resistance to antimicrobial PAE, which provide valuable information for controlling this fungus and AF biosynthesis in pre‐ and postharvest of agricultural crops.

lncRNA SNHG16 Mediates Cell Proliferation and Apoptosis in Cholangiocarcinoma by Directly Targeting miR-146a-5p/GATA6 Axis - Tao Wu; Ming-Sheng Lei; Xu-Zhao Gao; Ting-Gang Xiong; Kang Yang; Qian Gong; Rui Tang; Yue-Peng Tian; Xiao-Hua Fu (Biochemical Genetics, 2021)

CircRNA-23525 regulates osteogenic differentiation of adipose-derived mesenchymal stem cells via miR-30a-3p - Zeyou Guo; Luyang Zhao; Suhui Ji; Ting Long; Yanling Huang; Rui Ju; Wei Tang; Weidong Tian; Jie Long (Cell and Tissue Research, 2021)

Culturing novel and abundant pelagiphages in the ocean - Zefeng Zhang; Fang Qin; Feng Chen; Xiao Chu; Haiwei Luo; Rui Zhang; Sen Du; Zhen Tian; Yanlin Zhao (Environmental Microbiology, 2021)
Summary Viruses play a key role in biogeochemical cycling and host mortality, metabolism, physiology and evolution in the ocean. Viruses that infect the globally abundant SAR11 bacteria (pelagiphages) were reported to be an important component of the marine viral communities. Our current knowledge of pelagiphages is based on a few studies and therefore is limited. In this study, 10 new pelagiphages were isolated and genomically characterized. These pelagiphages represent the first cultivated representatives of four viral lineages only found in metagenomic sequencing datasets previously. Many abundant environmental viral sequences, i.e., single‐virus vSAG 37‐F6 and several Global Ocean Viromes (GOV) viral populations, are now further confirmed with these pelagiphages. Viromic read mapping reveals that these new pelagiphages are globally distributed in the ocean and can be detected throughout the water column. Remarkably, isolation of these pelagiphages contributed up to 12% of all viromic reads annotated in the analysed viromes. Altogether, this study has greatly broadened our understanding of pelagiphages regarding their morphology, genetic diversity, infection strategies, and distribution pattern. The availability of these newly isolated pelagiphages and their genome sequences will allow us to further explore their infectivities and ecological strategies.

High expression of long non-coding RNA Linc-A associates with poor survival in patients with colorectal cancer - Chong Zhao; Can Gan; Yang Xiao; Rui Liu; Linhao Zhang; Tian Lan; Yanting Ye; Huan Tong; Zhiyin Huang; Chengwei Tang; Jinhang Gao (Molecular Biology Reports, 2020)

TNF-α suppresses sweat gland differentiation of MSCs by reducing FTO-mediated m6A-demethylation of Nanog mRNA - Yihui Wang; Rui Wang; Bin Yao; Tian Hu; Zhao Li; Yufan Liu; Xiaoli Cui; Liuhanghang Cheng; Wei Song; Sha Huang; Xiaobing Fu (Science China Life Sciences, 2020)

Structural characterization and immunosuppressive activity of a new pregnane glycoside from Epigynum cochinchinensis - Yu-Ting Shao; Yan Zhao; Hong Zhang; Meng-Jun Jiang; Afsar Khan; Sheng-Bao Cai; Tian-Rui Zhao; Gui-Guang Cheng; Jian-Xin Cao (Natural Product Research, 2019)

Depositional facies and stratal cyclicity of carbonate successions in the Yingshan and Yijianfang Group (Lower-Middle Ordovician) in Yuejin-Tuoputai Region, Tarim Basin, NW China - Cunli Jiao; Zhao Xue-Qin; Rui Zhao; Li Hui-Li; Liu Tian-Jia; Zhao Jia-Hui (Carbonates and Evaporites, 2019)

Urinary bisphenol A (BPA) concentrations and exposure predictors among pregnant women in the Laizhou Wan Birth Cohort (LWBC), China - Shasha Zhao; Caifeng Wang; Rui Pan; Rong Shi; Weiye Wang; Ying Tian (Environmental Science and Pollution Research, 2019)

Comprehensive analysis of the whole coding and non-coding RNA transcriptome expression profiles and construction of the circRNA–lncRNA co-regulated ceRNA network in laryngeal squamous cell carcinoma - Rui Zhao; Feng-Qing Li; Lin-Li Tian; De-Si Shang; Yan Guo; Jia-Rui Zhang; Ming Liu (Functional & Integrative Genomics, 2019)

Isolation and purification of diterpenoids from the aerial parts of Isodon excisoides target-guided by UPLC-LTQ-Orbitrap-MS - Li-Ping Dai; Ling-Xia Zhang; Ya-Lin Liu; Hong Wu; Rui-Xin Liu; Meng Zhao; Shuang-Shuang Tian; Xue Jiang; Sui-Qing Chen (Natural Product Research, 2018)

Microsatellite records for volume 10, issue 1 - Ai-Qing Yu; Chengxin Fu; Chongbo He; Fei Liu; Guo-Hua Ding; Hongman Hou; Jian Zhao; Jianmin Yang; Jiansheng Wang; Kun-ci Chen; Lan-lan Zhang; Pan Li; et al. (Conservation Genetics Resources, 2018)

A new immunosuppressive pregnane glycoside from aqueous fraction of Epigynum cochinchinensis - Zong Wan; Yuan-Cheng Yao; Fei Gao; Sheng-Bao Cai; Afsar Khan; Tian-Rui Zhao; Xiao-Yan Yang; Jian Fan; Sheng-Yan Qian; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Seco-pregnane glycosides from the stems of Epigynum auritum - Fei Gao; Yuan-Cheng Yao; Zong Wan; Sheng-Bao Cai; Jian Fan; Tian-Rui Zhao; Jian-Xin Cao; Gui-Guang Cheng (Natural Product Research, 2017)

Hydrogen‐rich water regulates effects of ROS balance on morphology, growth and secondary metabolism via glutathione peroxidase in Ganoderma lucidum - Ang Ren; Rui Liu; Zhi‐Gang Miao; Xue Zhang; Peng‐Fei Cao; Tian‐Xi Chen; Chen‐Yang Li; Liang Shi; Ai‐Liang Jiang; Ming‐Wen Zhao (Environmental Microbiology, 2017)
Summary Ganoderma lucidum is one of the most important medicinal fungi, but the lack of basic study on the fungus has hindered the further development of its value. To investigate the roles of the redox system in G. lucidum , acetic acid (HAc) was applied as a reactive oxygen species (ROS) stress inducer, and hydrogen‐rich water (HRW) was used to relieve the ROS stress in this study. Our results demonstrate that the treatment of 5% HRW significantly decreased the ROS content, maintained biomass and polar growth morphology of mycelium, and decreased secondary metabolism under HAc‐induced oxidative stress. Furthermore, the roles of HRW were largely dependent on restoring the glutathione system under HAc stress in G. lucidum . To provide further evidence, we used two glutathione peroxidase (GPX)‐defective strains, the gpxi strain, the mercaptosuccinic acid (MS, a GPX inhibitor)‐treated wide‐type (WT) strain, and gpx overexpression strains for further research. The results show that HRW was unable to relieve the HAc‐induced ROS overproduction, decreased biomass, mycelium morphology change and increased secondary metabolism biosynthesis in the absence of GPX function. The gpx overexpression strains exhibited resistance to HAc‐induced oxidative stress. Thus, we propose that HRW regulates morphology, growth and secondary metabolism via glutathione peroxidase under HAc stress in the fungus G. lucidum . Furthermore, our research also provides a method to study the ROS system in other fungi.

Activation of Autophagy Contributes to the Angiotensin II-Triggered Apoptosis in a Dopaminergic Neuronal Cell Line - Qing Gao; Teng Jiang; Hong-Rui Zhao; Liang Wu; You-Yong Tian; Zhou Ou; Li Zhang; Yang Pan; Jie Lu; Ying-Dong Zhang (Molecular Neurobiology, 2016)

Identification of a Novel Rat NR2B Subunit Gene Promoter Region Variant and Its Association with Microwave-Induced Neuron Impairment - Li-Feng Wang; Da-Wei Tian; Hai-Juan Li; Ya-Bing Gao; Chang-Zhen Wang; Li Zhao; Hong-Yan Zuo; Ji Dong; Si-Mo Qiao; Yong Zou; Lu Xiong; Hong-Mei Zhou; et al. (Molecular Neurobiology, 2016)

α7nAChR is expressed in satellite cells at different myogenic status during skeletal muscle wound healing in rats - Zhi-Ling Tian; Shu-Kun Jiang; Miao Zhang; Meng Wang; Jiao-Yong Li; Rui Zhao; Lin-Lin Wang; Min Liu; Shan-Shan Li; Meng-Zhou Zhang; Da-Wei Guan (Journal of Molecular Histology, 2015)

Review and evaluation of China’s standards and regulations on the fuel consumption of motor vehicles - Yue-Fu Jin; Zhao Wang; Hui-Ming Gong; Tian-Lei Zheng; Xiang Bao; Jia-Rui Fan; Michael Wang; Miao Guo (Mitigation and Adaptation Strategies for Global Change, 2015)

Distance effect of matrix attachment regions on transgene expression in stably transfected Chinese hamster ovary cells - Jun-He Zhang; Xiao-Yin Wang; Tian-Yun Wang; Fang Wang; Wei-Hua Dong; Li Wang; Chun-Peng Zhao; Shu-Jie Chai; Rui Yang; Qin Li (Biotechnology Letters, 2014)

Detection of respiratory syncytial virus fusion protein variants between 2009 and 2012 in China - Qiuling Xia; Lili Zhou; Caijing Peng; Rui Hao; Ke Ni; Na Zang; Luo Ren; Yu Deng; Xiaohong Xie; Linli He; Daiyin Tian; Lijia Wang; et al. (Archives of Virology, 2014)

Constructing genetic linkage maps for Pinus elliottii var. elliottii and Pinus caribaea var. hondurensis using SRAP, SSR, EST and ISSR markers - Hui-xiao Yang; Rui Luo; Fen-cheng Zhao; Tian-yi Liu; Chun-xin Liu; Shao-wei Huang (Trees, 2013)

Lysobacter thermophilus sp. nov., isolated from a geothermal soil sample in Tengchong, south-west China - Da-Qiao Wei; Tian-Tian Yu; Ji-Cheng Yao; En-Min Zhou; Zhao-Qi Song; Yi-Rui Yin; Hong Ming; Shu-Kun Tang; Wen-Jun Li (Antonie van Leeuwenhoek, 2012)

Regulation of mesenchymal stem cell differentiation and insulin secretion by differential expression of Pdx-1 - Huijuan Yuan; Hongmei Liu; Rui Tian; Jie Li; Zhigang Zhao (Molecular Biology Reports, 2012)

Gel microbead cultivation with a subenrichment procedure can yield better bacterial cultivability from a seawater sample than standard plating method - Shiqi Ji; Rui Zhao; Qi Yin; Yuan Zhao; Chenguang Liu; Tian Xiao; Xiaohua Zhang (Journal of Ocean University of China, 2012)

Nicotinic acetylcholine receptor alpha7 subunit is time-dependently expressed in distinct cell types during skin wound healing in mice - Yan-Yan Fan; Tian-Shui Yu; Tao Wang; Wei-Wei Liu; Rui Zhao; Shu-Tao Zhang; Wen-Xiang Ma; Ji-Long Zheng; Da-Wei Guan (Histochemistry and Cell Biology, 2011)

Involvement of the ornithine decarboxylase/polyamine system in precondition-induced cardioprotection through an interaction with PKC in rat hearts - Ya-Jun Zhao; Wei-Hua Zhang; Chang-Qing Xu; Hong-Zhu Li; Li-Na Wang; Hong Li; Yi-Hua Sun; Yan Lin; Li-Ping Han; Li Zhang; Yie Tian; Rui Wang; et al. (Molecular and Cellular Biochemistry, 2009)